A Coupled-Fed Broadband Dual-Polarized Magnetoelectric Dipole Antenna for WLAN and Sub-6 GHz 5G Communication Applications - Sion Park; Sangkil Kim (Journal of Electromagnetic Engineering and Science, 2023)
This paper presents a novel coupled-fed broadband dual-polarized magnetoelectric dipole antenna for wireless local area network (WLAN) and 5G communication applications. The proposed magnetoelectric dipole antenna is composed of a planar electric dipole and shorting pins as a magnetic dipole to obtain a broad operation frequency band. Two coupled microstrip lines perpendicular to each other are coupled through a cross-shaped slot to excite the vertical and horizontal polarizations. The proposed antenna features a simple structure, high gain, and high polarization isolation. The measured impedance bandwidth of the proposed antenna is 1.8–4.2 GHz (fractional bandwidth of 80%). The measured realized antenna gain value is 3.7–8.5 dBi, and polarization isolation level is 25 dB at the operation frequency band.